PENGEMBANGAN VIDEO INTERAKTIF MATERI TEOREMA PYTHAGORAS UNTUK MEMFASILITASI NUMERASI SISWA SMPN 1 DEPOK YOGYAKARTA - Melissa, Margaretha Madha; Ningrum, Aria Prawira (Kadikma, 2024)
The purpose of this study was to develop interactive videos to facilitate numeracy and produce quality interactive video-based learning media products in terms of validity, practicality, and effectiveness. This research is a research and development study using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of this research were 31 students of class VIII F Junior High School 1 Depok Yogyakarta. Data collection techniques using validity questionnaires, numeracy tests, and teacher and student practicality questionnaires. Data from validation questionnaires, tests, and practicality questionnaires were analyzed quantitatively by calculating the average value. The results of this study are 1) The development of interactive videos using the ADDIE model. In the analysis stage, based on teacher interviews, students have difficulty understanding numeracy questions, the Pythagorean theorem material is a difficult topic, and teachers never used interactive videos in learning. At the design stage, researchers designed three videos using the Edpuzzle application. At the development stage, the learning product results were validated by three experts and revised according to the expert's suggestions. At the implementation stage, researchers conducted a trial of four meetings using the guided discovery model. In the evaluation stage, the product was valid, practical, and effective. 2) The product gets very valid results, in terms of media getting 91.25% and material getting 93%. Products get effective results from the numeracy test results as many as 29 students (93.5%) completed the minimum criteria (75). The practical product is seen from the results of the student response questionnaire to the media getting 85.8% and the teacher response questionnaire to the product getting 80%.